## Trending News

# This is just embarrassing..?

Solve by Factoring: 4x2 - 16 = 0

Solve by Factoring: 2x2 + 5x - 3 = 0

Solve by Factoring: x2 + 5x - 6 = 0

Solve by Factoring: 3x2 = -9x

I just picked up my kids text book and i can not do this it is frustrating that 15 year old is smarter than me!

Thank You now my kid wont have bragging rights hahaha

### 12 Answers

- Anonymous1 decade agoFavorite Answer
Go here to learn how to factor quadratics:

- ?Lv 71 decade ago
Solve by Factoring: 4x2 - 16 = 0, (2*x + 4)*(2*x - 4) = 0

Solve by Factoring: 2x2 + 5x - 3 = 0, (2*x - 1)*(x + 3)

Solve by Factoring: x2 + 5x - 6 = 0, (x + 6)*(x - 1)

Solve by Factoring: 3x2 = -9x , 3*x^2 + 9*x = 0, 3*x(x + 3) = 0

- 1 decade ago
1. 4x^2 - 16 = (2x)^2 - 4^2 = (2x+4) (2x-4)

2x+4 = 0, 2x-4 = 0

x = 2, -2

2. 2x^2 + 5x- 3 = (x+3) (2x-1)

x+3 =0, 2x-1=0

x = -3, 1/2

3. x^2 + 5x - 6 = (x+6) (x-1)

x + 6 = 0, x - 1 = 0

x = -6, 1

4. 3x^2 = -9x

3x^2 + 9x = 0

3x (x+3) = 0

3x = 0, x+3 =0

x = 0, -3

Note: In all cases, factorization can be done easily by finding two numbers whose sum is the coefficient of x term and product is the constant term (the one that does not contain x)

- Govind 3iLv 41 decade ago
4x2 - 16 = 0

==> (2x -4) (2x + 4) = 0

==> 2(x-2) (x+2) = 0

==> x = 2 or x = -2

x2 + 5x - 6 = 0

==> x^2 + 6x - x -6 = 0

==> x(x +6) -1(x+6) = 0

==> (x+6) (x -1) = 0

==> x = -6 or x = 1

3x2 = -9x

==> 3x^2 - 9x = 0

==> 3x(x -3) = 0

==> x = 3

- How do you think about the answers? You can sign in to vote the answer.
- ranjankarLv 71 decade ago
4x2 - 16 = 0

USE FORMULA a^2 - b^2 = ( a + b) ( a- b)

Here a = 2x

b = 4

( 2x + 4) ( 2x- 4 ) = 0

So EITHER

2x - 4 = 0

i.e. 2x = 4

x = 2

OR

( 2x + 4) = 0

2x = -4

x = -2

ANSWER x = +2 , -2

2) 2x^2 + 5x - 3 = 0

COEFF of x^2 = +2

( +2) ( -3) = -6

FIND FACTORS OF -6 which add up to + 5 ( COEFF of x )

(+6) ( -1)

2x^2 + 6x - x -3 = 0

2x ( x + 3) - 1( x + 3) = 0

( 2x -1) ( x+ 3) = 0

ANSWER x = -3, 1/2

3) x^2 + 5x - 6 = 0

x^2 + 6x - x - 6 = 0

x ( x + 6 ) -1 ( x + 6 ) = 0

( x - 1) ( x+ 6) = 0

ANSWER x = 1 , -6

4) 3x^2 = -9x

3x^2 + 9x = 0

3x ( x + 3) = 0

ANSWER x = 0 , -3

- Anonymous1 decade ago
4x2 - 16 = 0

4(x2 - 4) = 0

4(x - 2)(x + 2) = 0

x = 2, -2 --> This is because 4(2 - 2)(2 + 2) = 0 and 4(-2 - 2)(-2 + 2) = 0

2x2 + 5x - 3 = 0

(2x - 1)(x + 3) = 0

x = 1/2, -3

x2 + 5x - 6 = 0

(x - 1)(x - 5) = 0

x = 1, 5

3x2 = -9x

3x2 + 9x = 0

3x(x + 3) = 0

x = -3, 0

- TableNinja23Lv 41 decade ago
1. 4(x^2 - 4) = 0 = 4(x+2)(x-2), x = -2 or 2

2. (2x - 1)(x + 3) = 0, x = 1/2 or -3

3. (x + 6)(x - 1) = 0, x = -6 or 1

4. 3x^2 - 9x = 0 = 3x(x - 3), x = 0 or -3

- icemanLv 71 decade ago
4x^2 - 16 = 0

4(x^2 - 4) = 0

4(x + 2)(x - 2) = 0

x = -2, 2

x^2 + 5x - 6 = 0

(x + 6)(x - 1) = 0

x = -6, 1

- normanLv 71 decade ago
4(x^2-4) = 4(x+2)(x-2)=0 x = -2,2

(2x-1)(x+3)=0, x = 1/2, -3

(x+6)(x-1)=0, x=-6,1

3x^2 +9x = 0

3x(x+3) = 0, x=0, -3

- 1 decade ago
4(x^2-4)=0

4(x-2)(x+2)=0 x=2 x=-2

2x^2+5x-3=0

(2x-1)(x+3)=0 x=1/2 x=-3

x^2+5x-6=0 (x+6)(x-1)=0 x=-6 x=1

3x^2=-9x

x^2=-3x

x= +/- sq rt 3x

- runlolarunLv 41 decade ago
1 is 4 (x-2) (x+2) = 0

Solutions:

x = -2

x = 2

Use wolfram-alpha to solve all math problems

http://www30.wolframalpha.com/input/?i=4+x^2+-+16+...

2 is (x+3) (2 x-1) = 0

Solutions:

x = -3

x = 1/2

Source(s): http://www30.wolframalpha.com/input/?i=4+x^2+-+16+... http://www30.wolframalpha.com/input/?i=2x2+%2B+5x+...